Mitoapocynin Attenuates Organic Dust Exposure-Induced Neuroinflammation and Sensory-Motor Deficits in a Mouse Model - Massey, Nyzil; Shrestha, Denusha; Bhat, Sanjana Mahadev; Padhi, Piyush; Wang, Chong; Karriker, Locke A.; Smith, Jodi D.; Kanthasamy, Anumantha G.; Charavaryamath, Chandrashekhar (Frontiers in Cellular Neuroscience, 2022)
Increased incidences of neuroinflammatory diseases in the mid-western USA have been linked to exposure to agriculture contaminants. Organic dust (OD) is a major contaminant in the animal production industry and is central to the respiratory symptoms in the exposed individuals. However, the exposure effects on the brain remain largely unknown. OD exposure is known to induce a proinflammatory phenotype in microglial cells. Further, blocking cytoplasmic NOX-2 using mitoapocynin (MA) partially curtailed the OD exposure effects. Therefore, using a mouse model we tested a hypothesis that, inhaled OD induces neuroinflammation and sensory-motor deficits. Mice were administered with either saline or fluorescent LPS or OD extract intranasally daily for five days a week for five weeks. The saline or OD extract exposed mice received either a vehicle or MA (3 mg/kg) orally for three days/week for 5 weeks. We quantified inflammatory changes in the upper respiratory tract and brain, assessed sensory-motor changes using rotarod, open-field and olfactory test and quantified neurochemicals in the brain. Inhaled fluorescent LPS was detected in the nasal turbinates and olfactory bulbs. OD extract exposure induced atrophy of the olfactory epithelium with reduction in the number of nerve bundles in the nasopharyngeal meatus, loss of cilia in the upper respiratory epithelium with an increase in the number of goblet cells and increase in the thickness of the nasal epithelium. Interestingly, OD exposure increased the expression of HMGB1, 3-NT, IBA1, GFAP, p-Tau and TUNEL-positive cells in the brain. Further, OD exposure decreased time to fall (rotarod), total distance travelled (open-field test) and olfactory ability (novel scent test). Oral MA partially rescued olfactory epithelial changes and gross congestion of the brain tissue. MA treatment also decreased the expression of HMGB1, 3-NT, IBA1, GFAP, p-Tau and significantly reversed exposure induced sensory-motor deficits. Neurochemical analysis provided an early indication of depressive behavior. Collectively, our results demonstrate that inhalation exposure to OD can cause sustained neuroinflammation and behavior deficits through lung-brain axis and that mitoapocynin treatment can dampen the OD-induced inflammatory response at the level of lung and brain.